Data analytics usage, absorptive capacity and sharing economy innovation performance - Chua, Alton Yeow Kuan (2022)
This study investigates the usage of data analytics and absorptive capacity and its relationship to innovation performance in the context of the sharing economy. 127 survey responses from participants who held managerial positions or higher in organizations operating within the sharing economy were collected. A hierarchical regression analysis was conducted to assess the relationship between data analytic usage and absorptive capacity with innovation performance. Findings show that both data analytics usage and absorptive capacity are important to organizations operating in the sharing economy, with data analytic usage accounting for a higher variance in innovation performance.